Comparison of the efficacy of intravenous oxycodone versus morphine on postoperative pain following orthopaedics surgery under general anaesthesia - Sim, Chua Boon (2020)
Background Acute, severe postoperative pain is common following orthopaedics surgery and morphine is the commonest used intravenous opioid. The introduction of intravenous (IV) oxycodone has replaced morphine as the first choice of opioid used in postoperative pain management in some countries. The aim of this study is to assess the efficacy of IV oxycodone versus morphine on postoperative pain following orthopaedics surgery under general anaesthesia. Methods Fifty-eight American Society of Anesthesiologists (ASA) physical status I–II patients were randomly assigned to receive either 0.08 mg/kg IV oxycodone (Group O, n = 29) or 0.08 mg/kg morphine (Group M, n = 29) at the starting of skin closure. Postoperative pain was evaluated using a visual analogue scale (VAS) from at 0 min, hourly till 6th hour postoperatively. The time to first rescue analgesia, requirement of the first and second rescue analgesia and adverse effects were assessed. Results Postoperative pain score did not differ significantly in Group O and Group M from 0 min, hourly till 6th hour postoperatively (P > 0.950). There were no significant differences in the time to first rescue analgesia (P = 0.721), requirement of first (P = 0.594) and second rescue analgesia (P = 0.517) and adverse effects in both groups. Conclusion Intravenous oxycodone is equipotent to morphine in treating acute postoperative pain following orthopaedics surgery, and it is not associated with an increased risk of opioid related adverse events.